Perancangan UI/UX Aplikasi Mobile Debt Note Menggunakan Metode Double Diamond - Faris Afada (MULTINETICS, 2025)
Debt Note mobile application is designed to allow users to record the debts quickly and easily digitally, so that the information is easily accessible and well-organized. This design uses Double Diamond method which functions as a design framework that includes four phases: Discover, Define, Develop, and Deliver. The previous research has confirmed that Double Diamond method works well to improve UI/UX which can help in the design process systematically and refine solutions and ideas. This method helps to determine the needs of users and creating user interfaces (UI) and user experience (UX) to meet the expectations of users. This application is designed with simple and intuitive interface that allows users to easily track and manage debt transactions along with payment schedules. In the feasibility measurement process, this design uses System Usability Scale (SUS) by measuring user's satisfaction level based on 10 Likert-based scale statements. From the evaluation stage using System Usability Scale (SUS) method, the score value is shown with an average of 89.375. The results of this feasibility test are included in the Very Good category, which represents a positive response from users to the application design. The results of this study indicate that the interface design has a very good level of usability and is suitable for use.